Accumulation of Toxic Elements Disrupts Metabolic Processes in the Human: Review - Ali, Ali Adeeb (Journal of Biomedicine and Biochemistry, 2023)
Background Toxic elements are inorganic substances that do not have a physiological or functional role within the human body. Most metabolic processes are disrupted due to their accumulation through prolonged expo- sure to them from the environment. Toxic elements make up an extensive and very toxicologically dangerous group of substances. Usually, four el- ements are considered: Hg (mercury), Pb (lead), Cd (cadmium), and As (arsenic).Results Exposure to methylmercury has been associated with widespread neurological injury and diffuse encephalopathy. However, selec- tivity has been noted. The substance is toxic to some groups of nerve cells over others. Clinical signs of acute mercury exposure include Headache, nausea, and tremors. After chronic exposure, the onset of peripheral neu- ropathies has been described.Conclusion The accumulation of toxic heavy elements in general and cadmium, mercury, and lead (Pd) in particular leads to an imbalance in the metabolic processes and results in fat accumulation in the body. Thus, it causes obesity.